The Socialization of the Family Planning Village Program in Kuranji Banjarbaru - Mirza Noviani; Herry Porda Nugroho Putro; Muhammad Rezky Noor Handy (Universitas Lambung Mangkurat, 2023)
Population growth in the Banjarbaru City area has increased rapidly in recent years. Therefore it is necessary to have a family planning program. The family planning program is essential to implement because it contributes to suppressing abnormal population growth and strives for the population's quality so that it can increase. This service activity was carried out for four meetings in 1 round from November 21 to December 18 2022. The method used in this service activity consisted of counselling through a lecture and question and answer system and demonstrating the use of several contraceptives. Community service activities in Kuranji Village, Banjarbaru City, can run smoothly with participants of various ages and work well together during counselling.